2013
DOI: 10.1007/s00384-013-1663-3
|View full text |Cite
|
Sign up to set email alerts
|

Seven-year follow-up after anterior sphincter reconstruction for faecal incontinence

Abstract: Initially, both overall faecal incontinence and quality of life improved, but younger patients achieved a greater benefit. However, the results deteriorated with a longer follow-up. Operative management should be considered preferably in relatively young subjects as their results are better.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 19 publications
0
14
1
3
Order By: Relevance
“…Short-term follow-up of patients undergoing these procedures proves to be promising; however, the results do appear to diminish over time. 27,28 Lehto et al 29 demonstrated improvement in both overall fecal incontinence and quality of life in patients of all age ranges. However, younger patients achieved a greater benefit from surgery compared to their older counterparts.…”
Section: Correcting the Sphincter And Pelvic Floor Musclementioning
confidence: 97%
See 1 more Smart Citation
“…Short-term follow-up of patients undergoing these procedures proves to be promising; however, the results do appear to diminish over time. 27,28 Lehto et al 29 demonstrated improvement in both overall fecal incontinence and quality of life in patients of all age ranges. However, younger patients achieved a greater benefit from surgery compared to their older counterparts.…”
Section: Correcting the Sphincter And Pelvic Floor Musclementioning
confidence: 97%
“…These authors concluded that overlapping sphincteroplasty should be considered first-line therapy, specifically, in young patients with known sphincter defects given their improved short-and longterm results. 29 The Bflap valve mechanism^of fecal continence was first described by Parks in 1966. 30 The anterior wall of the rectum at the anorectal junction lies across the proximal part of the anal canal and creates a flap valve with increased intra-abdominal pressure.…”
Section: Correcting the Sphincter And Pelvic Floor Musclementioning
confidence: 99%
“…Many patients have favorable outcomes after sphincteroplasty [75][76][77]. However, long-term studies demonstrate that sphincter function deteriorates and previous improvement seen in continence decreases over time [76,77].…”
Section: Anal Sphincteroplastymentioning
confidence: 99%
“…However, patients are required to tolerate pain and there is a risk of complication. (7) Moreover, clinical sensing of such sickness is usually based on reduced defecation frequency or difficulty in defecation, which, however, always indicate that the patients are in a serious condition. Early diagnosis and a fast and painless treatment for fecal impaction are thus desirable.…”
Section: Introductionmentioning
confidence: 99%